Anesthesia in Patients With Multiple-System Atrophy: A Narrative Review and Practice Guidance. Issue 5 (1st March 2019) - Kumar, Chandra M.; Seet, Edwin; Singh, Rohit Kumar; Joshi, Girish P.
Abstract : Multiple-system atrophy, a rare adult-onset neurodegenerative disease, is associated with autonomic dysfunction, features of parkinsonism, and cerebellar ataxia. This article discusses multiple-system atrophy pathophysiology, clinical presentation, and perioperative issues pertinent to anesthesia.